(3eaJGM GdadGM aj Yed Gdjhe hGddjdIs - (3GdMGQKj GdYGedj GdgePGfj, HgGA GdOjf, eMeO Hf MSjf Hf YHO GdUeO, J (B1031(3g`s
(3ChdgG (B:s
(3GdMeO ddg GdPj OdfG Ydi LGOI GdfLGI(B...(3hHYO(B...(3bO GdJeS efj LeGYI ef ENhGf GdOjf hNdGf Gdjbjf JCja eNJUQ jMJhj Ydi eG dGHO dCgd GdOjGfI ef GdEJjGf Hg aj Gdjhe hGddjdI(B...s
(3BNQgG (B:s
...(3hceG aj bhdg Yf SdWGfg ZGaQ GdPfH hbGHd GdJhH TOjO GdYbGH Pj GdWhd MjK hMO UaI GdGfJbGe hLYdgG eMahaI HfYhJ GdYah hGdEMSGf(B...s
(3CJe JCdjag aj UaQ (B1105(3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B:(3L(B6(3,U(B102s
(3GdPQjYI(B:(3L(B21(3,U(B219(3,Qbe(B5375s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3GdJUha hGdBOGH GdTQYjIs